Effect of Credit to Farmers and Agricultural Productivity in Nigeria - Adewale, A.T; Lawal O.A; Aberu, F; Toriola A.K (East Asian Journal of Multidisciplinary Research, 2022)
In Nigeria, there has been a continuous decline in farmers access to credit facilities. This study examined the effect of farmers credit on agricultural productivity from 1981 to 2016 using data from World Bank Development Index (WDI). The result of the Ordinary Least Squares (OLS) estimation shows that agricultural bank credit (β=0.667173, t=5.961095 & P<0.05) exerts a significant positive effect on agricultural output. Bank lending rate (β=1.094792, t=1.295874 & P>0.05) and foreign exchange rate (β=0.124297, t=0.437929 & P>0.05) do not show a significant effect on agricultural output. It was submitted that bank credit has a significant positive effect on agricultural productivity in Nigeria. The need for government to promote savings and bank credit to farmers was recommended.